Andrić in hibridna identiteta - Vladušić, Slobodan (Slavistična revija, 2012)
This work is about the analysis of different concepts of hybrid identity that are represented in Andric's opus by characters such as doctor Cologne (Travnik's Chronicles) and Omerpasha Latas (Omerpasha Latas). Analysis of these characters shows that concept of hybrid identity is not monolithic and unambiguous due to different relationship that these characters have with ideaof humanity, institution of power and figure of convert.
Keywords: Andrić, Ivo; bosanska književnost; hibridna identiteta; identiteta; literarni liki; postkolonializem